City brand personality of Kuala Terengganu for image and reputation enhancement / Muhamad Fazil Ahmad - Ahmad, Muhamad Fazil (Faculty of Communication and Media Studies, 2018)
The purpose of the study is to develop a measure on the city branding of Kuala Terengganu as Coastal Heritage City using an Aaker’s brand personality scale. Specifically, the study proposes the antecedents of a city brand personality in promoting Kuala Terengganu City through it’s a strategic communication campaign. In order to administer this study, the qualitative and quantitative research methods were employed. In the first phase, semi-structured interviews and pre-test study were conducted to identify and verify the antecedents of city branding. In the second phase, survey questionnaires were applied using the Aaker’s brand personality scale. Finally, in the third phase, structured interviews were conducted to complement the results of the main studies. Five dimensions proposes with a total of nineteen (19) items from the City Personality Scale (CPS) that can be applied to the communication perspective in Malaysia. The five dimensions were refined using a confirmatory factor analysis and structural equation model. The factors were named as factor 1 (Peacefulness), factor 2 (Competence), factor 3 (Sophistication), factor 4 (Uniqueness) and factor 5 (Traditionalism). It seems the scale of 24 items brand personality to work better in the city branding among internal stakeholders (opinion leaders, communication managers, executives and non-executive officers). The results show that the revised brand personality is dire needed tailoring with Asian values. In fact, we found a cultural component is a strong predictor of City Brand Personality. The substantial contribution of this study is the City Brand Personality has successfully been developed in a Malaysian east coast context. Thus, this study may enrich current literatures on branding generally and city branding specifically in an Asian context.